Analisis Tantangan dan Peluang Perbankan Syariah di Kabupaten Sinjai - Syamsul; Muhammad Fajrin Adnan; Saiful Muchlis; Lince Bulutoding (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The Islamic banking and finance industry in Indonesia in general faces significant challenges and opportunities in the face of a growing competitive market. Although the majority of Indonesia's population is Muslim, this is not enough to support the development of the Islamic economy, especially Islamic financial institutions. Public awareness of Islamic banking and financial literacy is still very low. This implies that there are still many people who do not understand sharia principles in economic activities and align Islamic banks with conventional banks. Then, the lack of regulation and government support as well as sharia compliance are the main concerns of Islamic financial institutions. However, in the midst of these challenges, there are very potential opportunities for the Islamic banking and finance industry to grow and expand market reach. By increasing public awareness through socialization, literacy programs, providing adequate regulatory support, and implementing financial technology and strategic partnerships, this industry can make a greater contribution in strengthening the Indonesian economy in general and in Sinjai district in particular. In conclusion, these strategic measures will greatly assist the Islamic banking and finance industry in overcoming challenges and capitalizing on better future opportunities.